Bright and dark soliton stopping using nonlinear waveguide - Afroozeh, A.; Aziz, M. S.; Jalil, M. A.; Ali, J.; Yupapin, P. P. (My University, 2011)
In this study we propose an interesting system in which a bright and dark soliton pulse can be stopped within a nonlinear nanowaveguide. The system consists of micro and nano ring resonators, in which soliton pulse is input into the system and stopped pulse can be achieved within the nonlinear waveguide. A soliton input is chopped by the nonlinear effects into smaller pulses (chaos). The required pulse is filtered and amplified, which can be controlled and localized within the nonlinear waveguide. The localized bright and dark solitons are stopped by controlling the input power, which means that the photons stopping is controlled by light.
Keywords: Bright soliton; Dark soliton; Nonlinear nano waveguide; Stopped light